Influence of Pathogen Carbon Metabolism on Interactions With Host Immunity - Berguson, Hannah P.; Caulfield, Lauren W.; Price, Michael S. (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptococcus neoformans is a ubiquitous opportunistic fungal pathogen typically causing disease in immunocompromised individuals and is globally responsible for about 15% of AIDS-related deaths annually. C. neoformans first causes pulmonary infection in the host and then disseminates to the brain, causing meningoencephalitis. The yeast must obtain and metabolize carbon within the host in order to survive in the central nervous system and cause disease. Communication between pathogen and host involves recognition of multiple carbon-containing compounds on the yeast surface: polysaccharide capsule, fungal cell wall, and glycosylated proteins comprising the major immune modulators. The structure and function of polysaccharide capsule has been studied for the past 70 years, emphasizing its role in virulence. While protected by the capsule, fungal cell wall has likewise been a focus of study for several decades for its role in cell integrity and host recognition. Associated with both of these major structures are glycosylated proteins, which exhibit known immunomodulatory effects. While many studies have investigated the role of carbon metabolism on virulence and survival within the host, the precise mechanism(s) affecting host-pathogen communication remain ill-defined. This review summarizes the current knowledge on mutants in carbon metabolism and their effect on the host immune response that leads to changes in pathogen recognition and virulence. Understanding these critical interactions will provide fresh perspectives on potential treatments and the natural history of cryptococcal disease.